An Advanced High‐Entropy Fluorophosphate Cathode for Sodium‐Ion Batteries with Increased Working Voltage and Energy Density (Adv. Mater. 14/2022). Issue 14 (7th April 2022) - Gu, Zhen‐Yi; Guo, Jin‐Zhi; Cao, Jun‐Ming; Wang, Xiao‐Tong; Zhao, Xin‐Xin; Zheng, Xue‐Ying; Li, Wen‐Hao; Sun, Zhong‐Hui; Liang, Hao‐Jie; Wu, Xing‐Long
Abstract : Sodium‐Ion Batteries Cathode materials are decisive for the development of sodium‐ion batteries (SIBs). In article number 2110108, Xing‐Long Wu and co‐workers present a high‐entropy Na3 V2 (PO4 )2 F3 ‐based cathode for advanced SIBs. The high‐entropy effect endows this cathode material with a lowered Na + migration barrier and enhanced electronic conductivity, which jointly promote charge transport and sodium‐storage ability in the phosphate cathode, thereby enhancing the average operating voltage and energy density of the SIB.